Problem based learning case construct in undergraduate medical and nursing course: should there be difference? - Maharjan, Babu Raja; Devbhandari, Ranjan Prasad; Awale, Shanti; Pun, Khagi Maya (Journal of Patan Academy of Health Sciences, 2021)
Problem Based Learning (PBL) has been implemented in medical and nursing education programs to facilitate students’ deep learning. These two educational programs have some disciplines in common, but they have distinct educational outcomes. For these common disciplines to be congruent with the educational outcome, their respective curricula describe differences in their understanding level. Since the PBL case constructs largely determine the achievement of curricular objectives, they warrant a distinct approach while preparing a PBL case. Both the programs use clinical context for constructing PBL cases to deliver basic science content, but the focus needs to be turned towards their required clinical expertise. While PBL cases need to prioritize the diagnosis and treatment of the disease along with patient care for medical undergraduates, nursing undergraduates require focus on providing holistic nursing care, supporting and helping the patient during illness. This enables the understanding of basic science content comprehensively as applicable to their clinical practice.